Carson the Magnificent - Zehme, Bill 1958-2023; Thomas, Michael (Simon & Schuster, 2024)
Twenty years in the making, Zemhe and Thomas's book examines "one of the most inscrutable figures in entertainment history: a man who brought so much joy and laughter to so many millions but was himself exceedingly shy and private. Zehme traces Carson's rise from a magic-obsessed Nebraska boy to a Navy ensign in World War II to a burgeoning radio and TV personality to, eventually, host of The Tonight Show--which he transformed, along with the entirety of American popular culture, over the next three decades--